Global research trends on epigenetics and neuropathic pain: A bibliometric analysis - Zhu, Chenchen; Zhong, Weiquan; Gong, Chan; Chen, Binglin; Guo, Jiabao (Frontiers in Molecular Neuroscience, 2023)
Objective Neuropathic pain (NP) is a common disease that manifests with pathological changes in the somatosensory system. In recent years, the interactions of NP with the epigenetic mechanism have been increasingly elucidated. However, only a few studies have used bibliometric tools to systematically analyze knowledge in this field. The objective of this study is to visually analyze the trends, hotspots, and frontiers in epigenetics and NP research by using a bibliometric method. Methods Studies related to epigenetics and NP were searched from the Science Citation Index-Expanded of the Web of Science Core Collection database. Search time is from inception to November 30, 2022. No restrictions were placed on language. Only articles and reviews were included as document types. Data on institutions, countries, authors, journal distribution, and keywords were imported into CiteSpace software for visual analysis. Results A total of 867 publications met the inclusion criteria, which spanned the period from 2000 to 2022. Over the years, the number of publications and the frequency of citations exhibited a clear upward trend in general, reaching a peak in 2021. The major contributing countries in terms of the number of publications were China, the United States, and Japan. The top three institutions were Rutgers State University, Xuzhou Medical University, and Nanjing Medical University. Molecular Pain, Pain, and Journal of Neuroinflammation contributed significantly to the volume of issues. Among the top 10 authors in terms of the number of publications, Tao Yuan-Xiang contributed 30 entries, followed by Zhang Yi with 24 and Wu Shao-Gen with 20. On the basis of the burst and clusters of keywords, “DNA methylation,” “Circular RNA,” “acetylation,” “long non-coding RNA,” and “microglia” are global hotspots in the field. Conclusion The bibliometric analysis indicates that the number of publications related to epigenetics and NP is exhibiting a rapid increase. Keyword analysis shows that “DNA methylation,” “Circular RNA,” “acetylation,” “long non-coding RNA” and “microglia” are the most interesting terms for researchers in the field. More rigorous clinical trials and additional studies that explore relevant mechanisms are required in the future.